A comparison framework to support the selection of the best additive manufacturing process for specific aerospace applications - Garcia-Colomo, Alberto; Wood, Dudley; Martin, Filomeno; Williams, Stewart W. (Inderscience, 2020)
Additive Manufacturing (AM) is a cutting-edge technology that provides up to 100% of material efficiency and significant weight reduction which will positively impact aircraft fuel consumption in addition to high design freedom. Consequently, many aerospace companies are considering implementing AM thanks to these benefits. Therefore, the aim of this research is to assist aerospace organisations with a selection among different AM technologies. To enable this, primary data from (8) experts in the field of AM was collected through semi-structured interviews and cross-referenced with secondary data to identify the key factors for consideration in the selection of AM equipment for aerospace applications. Four AM technologies Laser Powder Bed Fusion (LPBF), Electron Beam Powder Bed Fusion (EBPBF), Wire Arc AM (WAAM) & Laser Metal Deposition (LMD) were highlighted by the experts as the most appropriate for aerospace applications. The main outcome of this study is the development of a comparison framework that helps companies select their AM technology depending on their main business or specific application.
Keywords: Additive Manufacturing; aerospace; business drivers; decision-making